BAHASA DI RUANG PUBLIK KOTA SINGKAWANG - Hari Purwiati; Eka Winarti (tuahtalino, 2016)
Singkawang is a multiethnic city with three major ethnic groups that exist,  Malay, Dayak, and Chinese however, that stands out is the Chinese culture. The diversity of culture, ethnicity and language presented through this research a variety of languages are written in a public space Singkawang. Data obtained by the method of observation. Observations of the research object in the banner, billboards and signage. Data collected by recording technique using cameras, exposure data and described by way of said, classifying, and analyzing it. The results of this study indicate that the condition of a multiethnic society gave rise to the existence of groups of people in the use of language in public space.